COGNITIVE AWARENESS AND GREEN GOVERNANCE IN ESG REPORTING QUALITY IMPROVEMENT - Ariyanto, Sanusi; Azwirman, Azwirman; Hamsal, Hamsal (Jurnal Akuntansi dan Keuangan Indonesia, 2026)
Background: This study examines how GRI adoption, green accounting, and green audit improve ESG reporting quality in Indonesian companies, while considering environmental unconsciousness as a cognitive moderator. Methods: A quantitative cross-sectional survey was conducted with 151 respondents from 37 companies that had adopted sustainability or ESG reporting practices. Data were analysed using Partial Least Squares Structural Equation Modelling with SmartPLS 4. Findings: GRI adoption, green accounting, and green audit have positive and significant effects on ESG reporting quality. Environmental unconsciousness also significantly moderates these relationships, showing that stronger environmental awareness helps companies translate internal sustainability mechanisms into credible and useful disclosures. Conclusions: ESG reporting quality depends on the integration of reporting standards, environmental accounting systems, assurance practices, and organisational cognition. Novelty/Originality of this article: This study develops an integrated framework that combines institutional, technical, assurance, and cognitive perspectives to explain ESG reporting quality in an emerging market context.